The Effect of Mechano-Chemical Activation of Fly Ash- Nanoparticle Blends on Performance of Cement Based Composites and Self-consolidating Concrete - (:unkn) unknown (My University, 2016)
Other than water, portland cement concrete is the most used commodity. Major parts of civil and transportation infrastructure, including bridges, roadway pavements, dams, and buildings are made of concrete. Because of wide-scale applications of these important structures in different climatic zones and associated exposures, concrete durability is often of major concern. In 2013, the study of American Society of Civil Engineers (ASCE) estimated that one-third of America’s major roads are in poor or mediocre condition [1]. The same article reports that annual investments of $170 billion on roads and $20.5 billion for bridges are needed to substantially improve the condition of infrastructure. In addition to durability concerns, the production of portland cement is associated with the emissions of approximately one cubic meter of carbon dioxide per ton (plus NOx and SOx). Therefore, replacement of portland cement with supplementary cementitious material is an important trend to improve the sustainability of concrete. Indeed, the consideration of these issues as well as proper and systematic design of concrete intended for highway applications is of extreme importance as concrete pavements represent up to 60% of interstate highway systems with heavier traffic loads. The combined principles of material science and engineering can provide adequate methods and tools to facilitate improvements to concrete design and existing specifications. Critically, durability and enhancement of long-term performance must be addressed at the design stage. Concrete used in highway pavement applications has relatively low cement content and also can be placed at low slump. However, further reduction of cement (cementitious materials) content to 280 kg/m3 vs. current specifications which require the use of 315 - 340 kg/m3 of cementitious materials for concrete intended for pavement applications and 335 kg/m3 for bridge substructure and superstructure needs a delicate proportioning of the mixture to maintain the expected workability, overall performance, and ensure long-term durability in the field. Such design includes, but is not limited to the optimization of aggregates and improvement of efficiency of supplementary cementitious materials (SCM), as well as fine-tuning of the type and dosage of chemical and air-entraining admixtures. Self-consolidating concrete (SCC) is a new type of concrete which is characterized by its ability to fill the formwork under its own weight without the use of vibration, while maintaining the homogeneity at a very low segregation. Self-consolidating concrete can flow easily under its own weight and is characterized by near zero yield value. Therefore, the design of SCC needs to minimize yield stress parameter which is different from conventional concrete. Better understanding the workability and flow behavior of developed SCC requires the investigation of the rheological response (shear stress and viscosity) of cement pastes of the same composition as SCC. For maintaining SCC workability it is essential to provide the adequate spacing between the aggregates in order to reduce friction between the particles. This is achieved by using mixtures with higher volumes of cement paste and the optimization of aggregates spacing, grading and proportions. The cement paste between the aggregates depends on the aggregate packing and is known as a compact paste (so it can be minimized by effective aggregates grading) while the cement paste surrounding the aggregates is known as excess paste. This excess paste allows concrete to flow and maintain a uniform dispersion [2]. The application of self-consolidating concrete (SCC) is focused on high performance, dense and uniform surface textures, improved durability, high strength and faster construction. The use of nanoparticles in SCC was a subject of interest for many researchers. Collepardi et.al [3] investigated low-heat self-consolidating concrete by combining supplementary cementing materials or SCM such as fly ash and limestone with colloidal nanosilica. In SCC, colloidal nanosilica acts as a viscosity modifying agent. Concrete was mixed, placed and consolidating without compaction and tested for slump flow and compressive strength. The performance of developed concrete was better in respect to slump flow and resistivity to segregation. In this study, SCC was developed using nanoparticles such as nanosilica and the effect of nanomaterials on the fresh and hardened properties of nano-engineered SCC was investigated. Furthermore, the SCC mixtures were designed with different proportions of fly ash used as with nanosilica and superplasticizer. In addition, for selected SCC mixtures, the use of activated fly ash was investigated to enhance the fresh properties and mechanical performance. The aggregate optimization was based on a computer simulation as reported previously. This research evaluated various theoretical and experimental methods for the design of the next generation of concrete for civil and infrastructure applications. For selected mixtures, reported research investigated eco-friendly concrete with cementitious materials content as low as 280 kg/m3 and self-consolidating concrete containing a total of 400 kg/m3 and 500 kg/m3 of cementitious materials, which can be an attractive alternative for the design of sustainable concrete pavements. This research demonstrated that nano-engineering of cementitious phase can be used as an effective tool to design a concrete with specific performance characteristics. For developed concrete, SCM, nanosilica and high range water reducing admixtures were selected based on the optimization study. The performance of different concrete mixtures was evaluated for fresh properties and compressive strength at the age from 1 and up to 90 days. The methods and tools discussed in this research are applicable, but not limited to wide range of concrete civil and transportation infrastructure. This research demonstrated modern approach to incorporate nano admixtures, activated SCM, the optimization of SCM (e.g., Class F and C fly ash), the use of modern superplasticizers (such as polycarboxylate ether, PCE). In new sustainable concrete, this research proved that the optimization of concrete mixture proportions for specific performance characteristics can be achieved by the use and proper selection of modern superplasticizers, nanosilica and ultrafine SCM. This optimization can result in an effective use of cementitious materials and provide substantial enhancement of performance. The effective use of supplementary cementitious materials (SCM) such as fly ash as partial replacement of portland cement is a very important strategy to reduce the environmental impact and improve the sustainability of conventional concrete. Many supplementary cementitious materials (SCM) are currently used in concrete improving the performance. Indeed, by-products such as fly ash can be recycled to produce “green” environmentally-friendly concrete with low cost. The proposed method to improve the performance of SCM is based on the use of nanotechnology and nanomaterials by engineering effective materials at nanolevel. Nanoparticles were found to improve the structure of conventional concrete, accelerate the formation of C-S-H and the development of early age strength, as well as improve the durability of cement based materials. To facilitate the distribution of nanoparticles, superplasticizing admixtures were investigated to reach the optimal dispersion. In order to increase the performance of cement systems with fly ash, the use of nanoparticles was proposed to boost the early age development. In this study, the combination of nano-engineered cement (NEC) concept and mechano-chemical activation (MCA) of fly ash with chemical admixtures is realized. The optimization of grinding conditions with AC (activated cement) in the vibrating mill in order to realize MCA has been performed. Due to intensive milling, very effective forms of AC are produced, as proved by the acceleration of heat of hydration of cement systems with AC. The proposed technique for AC uses the liquid state activation in order to facilitate the efficiency of long-term milling. It was proved that the use of mechanically activated composition resulted in the increase of early age compressive strength. The microstructure of AC was characterized using X-ray powder diffraction and scanning electron microscope (SEM). The compressive strength of mortars with activated fly ash was tested and compared with reference. The overall objective of reported study was to develop a new binding material concept based on mechano-chemical activation (MCA) of fly ash with the use of nanoparticles and effective application of developed binders in self-consolidating concrete (SCC). To analyze proposed concept, the following experimental steps were performed: 1. Optimization of the dosage of chemical admixtures using mortars; 2. Optimization of different types and sources of nanoparticles that can lead to the enhancement of properties of cement based materials; 3. Realization of NEC concept by activating of fly ash- nano particles blend in liquid state to produce finer activated blends; 4. Examination of the effect of activated fly ash on hydration, structure development and mechanical properties; 5. Development of an experimental matrix for comprehensive testing of chemical admixtures, SCM and activated fly ash blends in concrete including SCC; 6. Evaluation of the effect of fly ash and chemical admixtures on fresh properties and mechanical performance of reference (DOT-grade) concrete and SCC; 7. Investigation of the effects of fly ash – nanoparticle combination on flowability and resistance to segregation as well as strength development of eco-friendly SCC. Based on the established correlations, it was concluded that the use of nano-engineering approach and mechano-chemical activation of fly ash can provide an improved performance of different types of concrete. The enhanced concrete performance can be used as a tradeoff to reduce the portland cement and increase the volumes of SCM to compensate for portland cement component. The optimized superplasticized concrete with nanoparticles and with up to 30% of activated fly ash demonstrated very exceptional workability and mechanical performance. The proposed approach to engineer new concrete provided the material with enhanced performance, extended of life cycle, improved sustainability and environmental benefits.
Keywords: Concrete Material; Mechano-Chemical Activation; Nanoparticles; Self Consolidating Concrete; Strength; Sustainable Development